2009
DOI: 10.1136/gut.2009.178574
|View full text |Cite
|
Sign up to set email alerts
|

Human IgG antibody profiles differentiate between symptomatic patients with and without colorectal cancer

Abstract: IgG antibody profiles differentiate between symptomatic patients with and without colorectal cancer. Gut 2010;59:69-78.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

6
75
0

Year Published

2011
2011
2021
2021

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 63 publications
(81 citation statements)
references
References 54 publications
6
75
0
Order By: Relevance
“…In agreement with previous reports (26,27), we found that TCF3 is overexpressed in colon cancer tissues compared with adjacent noncancerous tissues. It has also been reported that TCF3 is highly expressed in various cancers, including prostate, gastric, and renal cancers (28)(29)(30).…”
Section: Discussionsupporting
confidence: 93%
See 1 more Smart Citation
“…In agreement with previous reports (26,27), we found that TCF3 is overexpressed in colon cancer tissues compared with adjacent noncancerous tissues. It has also been reported that TCF3 is highly expressed in various cancers, including prostate, gastric, and renal cancers (28)(29)(30).…”
Section: Discussionsupporting
confidence: 93%
“…The bHLH family member E12/E47 participates in the repression of E-cadherin expression and induction of the epithelial-to-mesenchymal transition, leading to the acquisition of invasive properties (24,25). Moreover, TCF3/E2A is overexpressed in colon cancer (26,27), prostate cancer (28,29), and renal cancer (30) and plays a critical role in the proliferation and survival of tumor cells (29). Consistent with these reports, we found that TCF3 was highly expressed in colon cancer tissues compared with the noncancerous tissues (Fig.…”
Section: Resultsmentioning
confidence: 99%
“…In the subjects with CEA level below 5 ng/mL, the classifier had a strong power in discriminating the CRC patients and the healthy controls, with an AUC of 0.975, indicating that the classifier might be able to fill in gaps of CEA in diagnosing early CRC. The classifier also has a higher validity than the reported arrays of some known CRC-associated antigens for the detection of CRC (21)(22)(23). Furthermore, OR for cases with the classification score more than 0.50 being associated with CRC was 99.0, which was much higher than an OR of 7.6 for G-FOBT and an OR of 18.7 for serum miR-92, the two methods recently reported for the early detection of CRC (28,29).…”
Section: Discussionmentioning
confidence: 99%
“…Profiling of circulating autoantibodies is therefore very attractive in diagnosing cancers at early stage. With the use of SEREX, protein array, and ELISA, autoantibodies to TAAs have been found in sera of the patients with CRC (14,(21)(22)(23). Although a panel of phage peptides developed by SEREX has high sensitivity and specificity in discriminating colon cancer patients with healthy controls, TAAs have not been fully identified (14).…”
Section: Introductionmentioning
confidence: 99%
“…TRIM21 also targets other factors that are responsible for type-I IFN activation, including IRF-5, IRF-7 and IRF-8, for degradation through proteasomal or, thus far, unknown mechanisms (Higgs et al, 2008(Higgs et al, , 2010Espinosa et al, 2009;Yoshimi et al, 2009;Young et al, 2011;Lazzari et al, 2014). TRIMs are often described as autoantigens in autoimmune diseases and cancers, including TRIM21 and TRIM68 in SLE and Sjögren syndrome (Der et al, 1998;Billaut-Mulot et al, 2001), TRIM33 in dermatomyositis and the associated paraneoplastic phenomena (Targoff et al, 2006;Fujimoto et al, 2012), TRIM19 in primary biliary cirrhosis (Stinton et al, 2011), and TRIM28 in colon cancer (Kijanka et al, 2010;Hector et al, 2012) and dermatomyositis (Satoh et al, 2012). Furthermore, TRIMs as a protein family have been associated with the regulation of type-I IFN responses (Versteeg et al, 2013), in keeping with relationships described for TRIM21 above .…”
Section: Role Of Trim-directed Precision Autophagy In Diseasementioning
confidence: 99%